Term structures of asset prices and returns - David Backus; Nina Boyarchenko; Mikhail Chernov (Federal Reserve Bank of New York, 2016)
We explore the term structures of claims to a variety of cash flows: U.S. government bonds (claims to dollars), foreign government bonds (claims to foreign currency), inflation-adjusted bonds (claims to the price index), and equity (claims to future equity indexes or dividends). Average term structures reflect the dynamics of the dollar pricing kernel, of cash flow growth, and of their interaction. We use simple models to illustrate how relationships between the two components can deliver term structures with a wide range of levels and shapes.
Keywords: G12; G13; 330; entropy; coentropy; term structure; yields; excess returns; Börsenkurs; Kapitalmarktrendite; Risikoprämie; Zinsstruktur; Kapitalmarkttheorie; Entropie; Theorie; Schätzung; Rentenmarkt; USA